Not Just for Kids: Child and Dependent Care Credit Benefits for Adult Care - Gabrielle Pepin; Yulya Truskinovsky (Institute of Labor Economics (IZA), 2024)
As the U.S. population ages, family caregivers face substantial out-of-pocket costs and financial risks while providing the majority of long-term care. The Child and Dependent Care Credit (CDCC), a tax credit based on income and care spending, subsidizes caregiving expenses but has low participation among adult caregivers. This paper evaluates the CDCC's current structure, documenting its limited impact on reducing caregiving costs and examining reforms to increase its utility for adult caregivers. Simulations of proposed changes—higher benefits, refundability, and relaxed eligibility requirements—demonstrate potential to expand access and enhance support for family caregivers within the existing policy framework.
Keywords: H24; J14; 330; adult care; Child and Dependent Care Credit; American Rescue Plan Act of 2021; participation; eligibility